2012
DOI: 10.3897/zookeys.176.2372
|View full text |Cite
|
Sign up to set email alerts
|

Cartographic analysis of woodlice fauna of the former USSR

Abstract: An inventory of the woodlice fauna of the former USSR yielded 190 species, 64 of them were recorded from the territory of Russia. According to the cartographic analysis, the limits of distribution of epigean terrestrial isopods over the area, excluding mountains, is explained by temperature. No woodlice records were found outside the isocline of 120 days a year with the mean daily air temperature >10°C. The highest species diversity was found between the isoclines of 180 and 210 days. These areas correspond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…An inventory of the woodlouse fauna of the former USSR yielded 190 species (Kuznetsova, Gongalsky 2012), but only 12 species were recorded from the territory of Kazakhstan. One species, Cylisticoides angulatus Schmalfuss, 2003, presented in the work of Kuznetsova, Gongalsky (2012) for the Astana area, is probably erroneous. This species was found to the west of the city of Astara in Azerbaijan (Schmalfuss 1989(Schmalfuss , 2003b, in the forest, and not in Astana (steppe zone).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An inventory of the woodlouse fauna of the former USSR yielded 190 species (Kuznetsova, Gongalsky 2012), but only 12 species were recorded from the territory of Kazakhstan. One species, Cylisticoides angulatus Schmalfuss, 2003, presented in the work of Kuznetsova, Gongalsky (2012) for the Astana area, is probably erroneous. This species was found to the west of the city of Astara in Azerbaijan (Schmalfuss 1989(Schmalfuss , 2003b, in the forest, and not in Astana (steppe zone).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Schmalfuss (2003b) indicates a probable record of this species near Sochi (authors comment: most likely it was introduced there), but the specimen was female, so there is no precise confirmation. Hemilepistus fedtschenkoi (Uljanin 1875) was recorded in Semipalatinsk (East Kazakhstan, steppe zone) (Kuznetsova & Gongalsky 2012). Three species, H. nodosus Budde-Lund, 1885; H. pavlovskii Borutzky, 1954;H.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Является одним из самых широко распространенных видов мокриц России (Kuznetsova and Gongalsky, 2012) и одним из самых обычных видов мокриц средней полосы Европы и Северной Америки (Залесская и Рыбалов, 1982). Наиболее многочислен в лесной и лесостепной зонах.…”
Section: семейство Trachelipodidae Strouhal 1953unclassified
“…The distributions of isopods at a macro scale are limited by natural factors, especially temperature and moisture (Harding andSutton 1985, Hopkin 1991). For example, a cartographic analysis of terrestrial isopods in the former USSR indicated that the length of the period with temperatures above 10 °C plays an important role in limiting isopod distributions (Kuznetsova and Gongalsky 2012). Lilleskov et al (2008) also found that the species richness of exotic terrestrial isopods in North America peaked at mid-latitudes (N40°).…”
Section: Environmental Factors Limiting Exotic Speciesmentioning
confidence: 99%